Analisis Work Life Balance Karyawan di Wirman Sambal - Kasmawati Kasmawati; Yobert Kornelius; Harnida Wahyuni adda; Suryadi Samudra (Pusat Riset dan Inovasi Nasional, 2024)
This research focuses on analyzing the work-life balance of employees at Usaha Wirman Sambal. In the context of the success of an organization, human resources play a crucial role. This business prioritizes the quality of chili sauce, requires employees with superior qualifications and optimal performance. Work-life balance is in the spotlight when facing complex work demands. This research is important because it impacts employee well-being, productivity and organizational competitiveness. Work-life balance is not just time allocation, but includes aspects of physical, mental health and the quality of social relationships. Increasing employee well-being contributes positively to productivity and performance. In the research